Slumdog romance: Facebook love and digital privacy at the margins. (April 2017) - Arora, Payal; Scheiber, Laura
Facebook has consolidated its position as the one-stop-shop for social activity among the poor in the global South. Sex, romance, and love are key motivations for mobile and Internet technology usage among this demographic, much like the West. Digital romance is a critical context through which we gain fresh perspectives on Internet governance for an emerging digital and globalizing public. Revenge porn, slut-shaming, and Internet romance scams are a common and growing malady worldwide. Focusing on how it manifests in diverse digital cultures will aid in the shaping of new Internet laws for a more inclusive cross-cultural public. In specific, this article examines how low-income youth in two of the BRICS (Brazil, Russia, India, China and South Africa) nations – Brazil and India – exercise and express their notions on digital privacy, surveillance, and trust through the lens of romance. This allows for a more thorough investigation of the relationship between sexuality, morality, and governance within the larger Facebook ecology. As Facebook becomes the dominant virtual public sphere for the world's poor, we are compelled to ask whether inclusivity of the digital users comes at the price of diversity of digital platforms.